Digital Innovation and Circular Economy in Islamic Basic Education: The IFDS-e M Model at SD Aisyiyah Gemolong - Murdiyanto, Murdiyanto; Cholily, Yus Mochamad; Syaifuddin, Mohammad (Jurnal Pendidikan Islam, 2025)
Purpose – This study investigates the implementation of Integrated Financial Digital Services and e-Money (IFDS-e M) as an innovation strategy to pioneer a circular school model at SD Aisyiyah Gemolong. It addresses Indonesia’s ecological crisis and unsustainable consumption patterns by combining digital transformation with circular economy principles in basic education. Design/methods/approach – Using a descriptive qualitative case study, the research was conducted at SD Aisyiyah Gemolong, a high-performing elementary school with 1,030 students in Central Java. Data were collected through participatory observation, in-depth interviews, documentation, and questionnaires. Data analysis employed the Miles and Huberman model to interpret emerging patterns and evaluate program impact. Findings – The IFDS-e M system successfully digitized school transactions, reduced the use of cash, and shaped environmentally conscious behaviors among students. The ban on pocket money led to a measurable reduction in food packaging waste, while school-owned enterprises (BUMS) enhanced service efficiency and internal resource circulation. Over 95% of school financial transactions were processed digitally, improving transparency and minimizing paper use. Challenges such as intermittent internet connectivity emerged during peak access times but did not hinder overall program outcomes. Research implications – The IFDS-e M model offers a replicable strategy for schools to advance sustainable behavior and reduce environmental impact. It informs educational policy and practice on integrating digital tools with ecological values to cultivate responsible consumption from an early age.